Comprehensive Genomic Profiling of High-Risk Pediatric Cancer Patients Has a Measurable Impact on Clinical Care. (11th May 2022) - Summers, Ryan J.; Castellino, Sharon M.; Porter, Christopher C.; MacDonald, Tobey J.; Basu, Gargi D.; Szelinger, Szabolcs; Bhasin, Manoj K.; Cash, Thomas; Carter, Alexis B.; Castellino, Robert Craig; Fangusaro, Jason R.; Mitchell, Sarah G.; et al.
Abstract : PURPOSE: Profiling of pediatric cancers through deep sequencing of large gene panels and whole exomes is rapidly being adopted in many clinical settings. However, the most impactful approach to genomic profiling of pediatric cancers remains to be defined. METHODS: We conducted a prospective precision medicine trial, using whole-exome sequencing of tumor and germline tissue and whole-transcriptome sequencing (RNA Seq) of tumor tissue to characterize the mutational landscape of 127 tumors from 126 unique patients across the spectrum of pediatric brain tumors, hematologic malignancies, and extracranial solid tumors. RESULTS: We identified somatic tumor alterations in 121/127 (95.3%) tumor samples and identified cancer predisposition syndromes on the basis of known pathogenic or likely pathogenic germline mutations in cancer predisposition genes in 9/126 patients (7.1%). Additionally, we developed a novel scoring system for measuring the impact of tumor and germline sequencing, encompassing therapeutically relevant genomic alterations, cancer-related germline findings, recommendations for treatment, and refinement of risk stratification or prognosis. At least one impactful finding from the genomic results was identified in 108/127 (85%) samples sequenced. A recommendation to consider a targeted agent was provided for 82/126 (65.1%) patients. Twenty patients ultimately received therapy with a molecularly targeted agent, representing 24% of those who received a targeted agent recommendation and 16% of the total cohort. CONCLUSION: Paired tumor/normal whole-exome sequencing and tumor RNA Seq of de novo or relapsed/refractory tumors was feasible and clinically impactful in high-risk pediatric cancer patients.